2010
DOI: 10.1002/adem.201080003
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Carbonate–Hydroxyapatite Nanocrystals Prepared by Vapor Diffusion

Abstract: Biomimetic carbonate–hydroxyapatite (HA) nanocrystals have been synthesized by using the sitting drop vapor diffusion technique, for the first time. The method consists of diffusing vapors of an aqueous solution of NH4HCO3 through drops containing an aqueous mixture of (CH3COO)2Ca and (NH4)2HPO4 in order to increase slowly their pH. This synthesis has been performed in a crystallization mushroom, a glass device developed for protein and small molecules crystallization. The concentrations of the reagents, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 36 publications
6
51
3
Order By: Relevance
“…After treatment, bands assigned to COO − symmetric stretching and OH bending of COOH became apparent at 1,400 and 1,250 cm −1 , respectively. On the other hand, the intensity of the band at 1,340 cm −1 assigned to C-OH stretch was significantly decreased 16,17) . These results mean that PGA was immobilized on the surface of the chemically synthesized collagen.…”
Section: Methodsmentioning
confidence: 99%
“…After treatment, bands assigned to COO − symmetric stretching and OH bending of COOH became apparent at 1,400 and 1,250 cm −1 , respectively. On the other hand, the intensity of the band at 1,340 cm −1 assigned to C-OH stretch was significantly decreased 16,17) . These results mean that PGA was immobilized on the surface of the chemically synthesized collagen.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, nanodimensional HA might be manufactured by a laser-induced fragmentation of HA targets in water [463][464][465][466][467] and in solvent-containing aqueous solutions [344,371,468], while dense nanocrystalline HA films might be produced by radio frequency magnetron sputtering [469,470]. An interesting approach using sitting drop vapor diffusion technique should be mentioned as well [471]. A comparison between the sol-gel synthesis and wet chemical precipitation technique was performed and both methods appeared to be suitable for synthesis of nanodimensional apatite [328].…”
Section: Nanodimensional and Nanocrystalline Apatitesmentioning
confidence: 99%
“…Despite the large number of synthetic strategies to synthesize nanoapatites, the preparation of HA with similar physico-chemical and morphological characteristics to those of the bone mineral phase, still remains an intellectual and technological challenge [4]. Recently, Iafisco et al reported a new methodology, based on the vapour diffusion sitting drop micro-method, to precipitate carbonate-substituted hydroxyapatite nanoparticles [5]. The method was developed by using an innovative device called the "crystallization mushroom" [6].…”
Section: Introductionmentioning
confidence: 99%